2018
DOI: 10.1016/j.ymgme.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of echocardiographic abnormalities in mucopolysaccharidosis III

Abstract: Individuals with Sanfilippo A and B demonstrate a natural history of cardiac involvement with valvular abnormalities most common. In short-term follow up, patients demonstrated only mild progression of abnormalities, none requiring intervention. Valvular disease prevalence is similar to MPS I and II, but appears less severe. These findings raise no specific concerns for gene transfer trials in patients in this age range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…In all cases the affected valves were the mitral and aortic valve. This is in line with previous studies in MPS III and other MPSs . Both the aortic valve and the mitral valve mainly showed an insufficiency.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In all cases the affected valves were the mitral and aortic valve. This is in line with previous studies in MPS III and other MPSs . Both the aortic valve and the mitral valve mainly showed an insufficiency.…”
Section: Discussionsupporting
confidence: 93%
“…While CD was previously not considered to be present in MPS III, several recent studies reported cardiac involvement . In addition, CD may also be related to sudden unexpected death reported in some patients …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…At an early age, MPS III patients are typically taller with an increased head circumference compared to healthy children, but their growth slows around 5 years of age and by their late teens they are generally shorter than average [41]. Cardiac involvement may be present, consisting typically of mild abnormalities in cardiac valves [32,42].…”
Section: Neurobehavioral Abnormalities and Cognitive Decline As The Mmentioning
confidence: 99%
“…Patients with MPS III generally appear unaffected at birth, however clinical manifestations may emerge from 2 to 4 years of age, including intellectual disability, hyperactivity, coarse facial features with broad eyebrows, hirsutism, skeletal dysplasia, degenerative joint disease, hepatosplenomegaly, macrocephaly, and hearing loss [1, 1921]. Cardiac abnormalities have been observed in patients with all types of MPS, except MPS IX [213], however only a few studies have focused on cardiac alterations in patients with MPS III [2225]. A murine model of MPS IIIB (NAGLU knockout mice, NAGLU −/− ) demonstrated the development of abnormal valve morphology and function in an age-dependent manner associated with increased myocardial vacuolization, inflammation and fibrosis, as well as a dysregulated lysosomal autophagy in the cardiac tissues [26].…”
Section: Introductionmentioning
confidence: 99%